Amylin receptors: molecular composition and pharmacology. (26th October 2004) - Hay, D.L.; Christopoulos, G.; Christopoulos, A.; Sexton, P.M.
Abstract : Several receptors which bind the hormone AMY (amylin) with high affinity have now been identified. The minimum binding unit is composed of the CT (calcitonin) receptor at its core, plus a RAMP (receptor activity modifying protein). The receptors have been named AMY1(a), AMY2(a) and AMY3(a) in accordance with the association of the CT receptor (CT(a) ) with RAMP1, RAMP2 and RAMP3 respectively. The challenge is now to determine the localization and pharmacological nature of each of these receptors. Recent attempts to achieve these aims will be briefly discussed.